2019
DOI: 10.1038/s41559-019-0871-9
|View full text |Cite|
|
Sign up to set email alerts
|

Ancient genomes indicate population replacement in Early Neolithic Britain

Abstract: The roles of migration, admixture and acculturation in the European transition to farming have been debated for over 100 years. Genome-wide ancient DNA studies indicate predominantly Aegean ancestry for continental Neolithic farmers, but also variable admixture with local Mesolithic hunter-gatherers. Neolithic cultures first appear in Britain ca. 4000 BCE, a millennium after they appear in adjacent areas of continental Europe. The pattern and process of this delayed British Neolithic transition remains unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
223
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(242 citation statements)
references
References 50 publications
17
223
1
1
Order By: Relevance
“…Advances in next-generation sequencing technologies and the emergence of full genome characterisation of archaeological samples however now suggest that LP may not have been prevalent in the Neolithic, but instead present only in very low frequencies across the population, if present at all. The absence of LP in European Neolithic populations has now been noted in a number of studies (e.g., Burger et al 2007;Gamba et al 2014;Witas et al 2015;Olalde et al 2018;Brace et al 2019), and Allentoft et al (2015) suggest that LP had a very low frequency (5-10%) even in Bronze Age European populations, indicating that LP is the result of more recent positive selection. Similarly, a large-scale study by Mathieson et al (2015) suggests that LP in Europe only became under strong selection within the last 4000 years.…”
Section: Lactase Persistence and The Origins Of Milk Consumptionmentioning
confidence: 89%
See 1 more Smart Citation
“…Advances in next-generation sequencing technologies and the emergence of full genome characterisation of archaeological samples however now suggest that LP may not have been prevalent in the Neolithic, but instead present only in very low frequencies across the population, if present at all. The absence of LP in European Neolithic populations has now been noted in a number of studies (e.g., Burger et al 2007;Gamba et al 2014;Witas et al 2015;Olalde et al 2018;Brace et al 2019), and Allentoft et al (2015) suggest that LP had a very low frequency (5-10%) even in Bronze Age European populations, indicating that LP is the result of more recent positive selection. Similarly, a large-scale study by Mathieson et al (2015) suggests that LP in Europe only became under strong selection within the last 4000 years.…”
Section: Lactase Persistence and The Origins Of Milk Consumptionmentioning
confidence: 89%
“…The British Neolithic is a period which has long been characterised by the arrival and adoption of agriculture and perceived associated sedentary lifestyle, alongside the emergence of new forms of material culture and the construction of a range of monumental forms. Most recently, more support for the hypothesis that this 'Neolithic package' was brought to Britain by incoming European farmers has been recognised (Brace et al 2019). Importantly, the Neolithic heralds a significant shift in subsistence, characterised by the introduction of domesticates into Britain, which included emmer wheat (Triticum dicoccum), einkorn wheat (Triticum momococcum) and barley (Hordeum vulgare), alongside emerging animal husbandry of domesticated species-predominately cattle, pig, sheep and goats (Thomas 1999;Rowley-Conwy 2004;Brown 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of cereals into and Ireland (c. 3750 cal BC) appears to have been a rapid and widespread process ). This does not provide evidence for migration per se, but rather it is more consistent with models favouring colonisation by farming communities at the onset of the Neolithic (eg, Rowley-Conwy 2004;Sheridan 2010;McLaughlin et al 2016;Brace et al 2019). However, a balance between migration and acculturation by indigenous hunter-gatherers should not be overlooked (eg, Whittle et al 2011;Thomas 2014).…”
mentioning
confidence: 60%
“…To address this in more detail, direct AMS radiocarbon dating of cereals from sites in Wales is required to assess the timing of their introduction and its relationship to wider changes in the archaeological record (Griffiths 2018). Other lines of evidence provide compelling evidence for migration in this period including strontium isotope analyses of Early Neolithic human remains in south-east Wales (Neil et al 2017) and large-scale aDNA studies (Brace et al 2019). A sharp demographic increase coeval with the introduction of farming in Britain and Ireland is also indicated McLaughlin et al 2016), possibly during a period of warming climate (Warden et al 2017;cf.…”
Section: Early Neolithic: the Introduction Of Cerealsmentioning
confidence: 99%
“…In 2018, researchers from the museum exploded this stereotype using next‐generation sequencing on a new DNA sample extracted from the temporal bone. Archeologist Tom Booth, one of the museum researchers and now a staffer in the Ancient Genomics Laboratory at the Francis Crick Institute in London, said the new findings suggest that Cheddar Man had a dark‐to‐black complexion, dark wavy or curly hair, and blue eyes . The data also showed that Cheddar man was lactose‐intolerant; he could not digest milk, which is a less common trait in Europeans.…”
Section: Rewriting Historymentioning
confidence: 99%